Design and simulation of a low return loss UWB CPW-fed patch antenna for mobile wireless communications - Abbaoui Hind; Ghammaz Abdelilah; Belahrach Hassan; El Bakouchi Raefat-Jalila (ITM Web of Conferences, 2023)
With the recent development of wireless communication systems and the 5G spectrum, mobile broadband technology (MBB) has been thriving. In this contribution, the design of an Ultra Wide Band T-slotted rectangular microstrip patch antenna is presented which is suitable for high data rate applications. The antenna is fed using a coplanar waveguide and is designed for two central operating frequencies, the lower resonant frequency at 3.6 GHz, an internationally recognized standard for 5G wireless mobile communications and a higher frequency at 6.8 GHz, which is part of the new wifi-6E standards. All data of the characteristic parameters have been obtained by using the Computer Simulation Technology Microwave Studio Student suite 2021 (CST MWS).